Perceptions of business ethics in a multicultural community: the case of Malaysia - Abdul Rashid, Md. Zabid; Ho, Jo Ann (Kluwer Academic Publishers, 2003)
This paper examines the perceptions of the Malays, Chinese and Indian managers and executives on business ethics in Malaysia. Based on twenty-four hypothetical business situations, 161 respondents participated in the study. Discriminant analysis was used to determine the differences in the perceived business ethics among the Malays, Chinese and Indian respondents. The overall results of the classification matrix showed that 65.2% of the twenty-four business ethics were correctly classified according to Malays, Chinese, and Indian groups. However, the classification matrix for their perceptions on issues relating to consumers showed that 55.3% of the six issues on ethics were correctly classified, while the results for the issues relating to employees were 67.7% of the twelve issues were correctly classified. The results for the issues relating to suppliers showed that 59.6% of the six issues were correctly classified. These findings suggest that ethnic groups have some influence on the perceived business ethics. The implications of the findings are also discussed.